Simple and Specific Grafting of Antibacterial Peptides on Silicone Catheters. Issue 23 (28th October 2016) - Pinese, Coline; Jebors, Said; Echalier, Cécile; Licznar‐Fajardo, Patricia; Garric, Xavier; Humblot, Vincent; Calers, Christophe; Martinez, Jean; Mehdi, Ahmad; Subra, Gilles
Abstract : To fight against nosocomial infection initiated by colonization of medical devices, a strategy enabling the direct and fast functionalization of silicone surfaces is proposed. This strategy proceeds in a site‐specific way using original hybrid silylated antibacterial peptides. This safe and up‐scalable method guarantees a covalent and robust immobilization with the correct orientation of the bioactive moiety. Importantly it also avoids multi‐step chemical modifications of the surface or multi‐layer polymer coatings. As proof of concept, antibacterial silicone catheter has been prepared whose immediate and long term efficiency is superior by comparison to similar silver‐embedded materials. Abstract : A strategy enabling the direct and fast functionalization of silicone surfaces with antibacterial peptides is developed. Thanks to hybrid silylated bioactive molecules, no multi step surface modifications or polymer coating are required. Antibacterial silicone catheters are obtained and proved to be more efficient than commercially available silver‐embedded devices.